2015
DOI: 10.1039/c5ra13672e
|View full text |Cite
|
Sign up to set email alerts
|

Effect of graphene on the self-assembly and rheological behavior of a triblock copolymer gel

Abstract: The self-assembly behavior of physical gels and the effect of such an assembly on the mechanical properties are of significant interest. Here, graphene nanoplatelets have been incorporated in a triblock copolymer gel consisting of poly(methyl methacrylate)-poly(n-butyl acrylate)-poly(methyl methacrylate)[PMMA-PnBA-PMMA] in a midblock selective solvent, 2-ethyl-1-hexanol. The thermoreversible nature of the gel allowed us to incorporate the graphene nanoplatelets in a liquid stage and these nanoplatelets then be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
77
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(81 citation statements)
references
References 35 publications
(109 reference statements)
4
77
0
Order By: Relevance
“…All these differences can be explained in terms of a slight difference in the PMMA solubility parameter in two solvents chosen here. The difference in total solubility parameters (Hilderbrand) between PMMA and 2‐ethyl‐1‐hexanol is 2.59, which is larger than 0.41, the difference between PMMA and n ‐butanol (see Table S1 in SI) …”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…All these differences can be explained in terms of a slight difference in the PMMA solubility parameter in two solvents chosen here. The difference in total solubility parameters (Hilderbrand) between PMMA and 2‐ethyl‐1‐hexanol is 2.59, which is larger than 0.41, the difference between PMMA and n ‐butanol (see Table S1 in SI) …”
Section: Resultsmentioning
confidence: 94%
“…For example, in the case of a strong association, during deformation the chains can be stretched to their full length before being pulled out of the aggregates. In those instances, distinct strain‐stiffening responses have been observed …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For physical gels, stress relaxes through breaking and reforming of physical bonds . The data on the stress relaxation at different temperatures were fitted using the Kohlrausch's stretched exponential relaxation model (Equation ) G(t)=G0exp[(t/τ)β], 0<β<1 where τ is the characteristic relaxation time, G 0 is the plateau modulus, and β is the relaxation exponent. The results show that the stress relaxation time followed the Arrhenius behavior (Figure d) with E a of ≈144 ± 4 kJ mol −1 as calculated using the following equation.…”
Section: Resultsmentioning
confidence: 99%
“…When the value of χ is less than that of the upper critical limit, miscibility is favored. [ 33,34 ] In this study, we exploited this high-temperature induced-phase miscibility of lignin and NBR-41 by shearing the mixture at 160 °C long enough to cause some degree of chemical reactivity. Coleman and co-workers [ 32 ] have shown that for components having weak and moderate hydrogen bonding, the critical χ values are about 0.02-0.2 and 0.2-1.0 [corresponding Δ δ 's are 1.0-2.0 and 2.0-5.1 (MPa) 0.5 ], respectively.…”
Section: Process Engineeringmentioning
confidence: 99%